The Thatcher decade : how Britain has changed during the 1980s. - Riddell, Peter (Oxford : Basil Blackwell, 1989)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: Thatcher, Margaret; Groot-Brittannië.